Numerical Simulation of Cyclone Efficiency and Pressure Drop - Gimbun, Jolius (2004)
The Department of Environment Malaysia (DOE) has been regulating particulate emission since the 1978. More stringent environmental regulations have resulted in considerable research into ways of reducing harmful and gloomy particulate emissions. Cyclones are probably the most commonly used means of separating dust from gases, controlling pollution, collecting particulate product or recovering catalyst particles from fluidised reactors. Their popularity is due to low maintenance and investment costs. Cyclone design maybe simple but models use to predict the cyclone efficiency and pressure drop are not always accurate. The objective of this study is to carry out simulation via a commercial spreadsheet, MS EXCEL and CFD code FLUENT 6.1, on cyclone design, efficiency, and pressure drop for particulate emission control. In this study, CFD code FLUENT and four cyclone collection models earlier developed by other researchers are used for prediction of cyclone efficiency. This study focuses on various operating conditions of cyclone and the simulation result is then verified via experimental data published in the literature. The model with the best prediction on experimental data is then used to evaluate the effects of cyclone configuration, dimension, and variable on its collection efficiency. The cyclone pressure drop calculations are performed using CFD and empirical models adopted from the literature. These four empirical models and CFD are compared with presented experimental data available in the literature.All the modelling and simulation of cyclone efficiency and pressure drop are proved to be satisfactory when compared with the presented experimental data. The CFD simulations and Li and Wang model predict excellently the cyclone cut-off size for all operating conditions with a deviation of 3 and 6% from the experimental data respectively. The CFD simulations also predict excellently the cyclone pressure drop under different temperature and inlet velocity with a maximum deviation of 3% from the experimental data. Specifically, results obtained from the computer modelling exercise have demonstrated that CFD and Li and Wang model is a best method of modelling cyclones collection efficiency and pressure drop. The result or finding obtained from the research work can be used to develop a cyclone with greater separation efficiency, which is capable of removing up to 99% of PM5. This cyclone can then be used for particulate pollutant control from industrial factory to the atmosphere.